A reverse engineering approach to framework comprehension - Campo, Marcelo (1997)
Framework comprehension is a very limiting factor to take full advantage of the benefits that frameworks offer to increase quality and productivity in software development. In this paper, a reverse engineering approach to framework comprehension using the MetaExplorer tool is presented. MetaExplorer is characterized by the use of meta-objects to gather information from framework applications, providing a rich set of visualizations, and abstraction capabilities for subsystem analysis and design-patterns recognition, along with advanced exploration mechanisms based on semantic zooming and direct-manipulation user interfaces. The effectiveness the tool to help on the process of framework understanding was tested through controlled experiments, whose metrics suggest that users of the tool grasp a much better understanding of an analyzed framework than users not using the tool.